Induction and repression of DAN1 and the family of anaerobic mannoprotein genes in Saccharomyces cerevisiae occurs through a complex array of regulatory sites - Cohen, Brian D. (Oxford University Press, 2001)
The DAN/TIR mannoprotein genes of Saccharomyces cerevisiae (DAN1, DAN2, DAN3, DAN4, TIR1, TIR2, TIR3 and TIR4) are expressed in anaerobic cells while the predominant cell wall proteins Cwp1 and Cwp2 are down-regulated. Elements involved in activation and repression of the DAN/TIR genes were defined in this study, using the DAN1 promoter as a model. Nested deletions in a DAN1/lacZ reporter pinpointed regions carrying activation and repression elements. Inspection revealed two consensus sequences subsequently shown to be independent anaerobic response elements (AR1, consensus TCGTTYAG; AR2, consensus AAAAATTGTTGA). AR1 is found in all of the DAN/TIR promoters; AR2 is found in DAN1, DAN2 and DAN3. A 120 bp segment carrying two copies of AR1 preferentially activated transcription of lacZ under anaerobic conditions. A fusion of three synthetic copies of AR1 to MEL1 was also expressed anaerobically. Mutations in either AR1 site within the 120 bp segment caused a drastic loss of expression, indicating that both are necessary for activation and implying cooperativity between adjacent transcriptional activation complexes. A single AR2 site carried on a 46 bp fragment from the DAN1 promoter activated lacZ transcription under anaerobic conditions, as did a 26 bp synthetic AR2 fragment fused to MEL1. Nucleotide substitutions within the AR2 sequence eliminated the activity of the 46 bp segment. Ablation of the AR2 sequences in the full promoter caused a partial reduction of expression. The presence of the ATTGTT core (recognized by HMG proteins) in the AR2 sequence suggests that an HMG protein may activate through AR2. One region was implicated in aerobic repression of DAN1. It contains sites for the heme-induced Mot3 and Rox1 repressors.